2019
DOI: 10.1080/02670844.2018.1557996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MgO micro-powder on the characteristics of micro-arc oxidation coatings

Abstract: MgO micro-powder of different concentrations from 0 to 8 g L −1 was added in the electrolyte. Effects of MgO micro-powder concentration on properties of micro-arc oxidation (MAO) coating were analysed by scanning electron microscopy, energy dispersive spectrometer, X-ray diffraction, electrochemical workstation, thermal shock tester equipment, etc. The result revealed that the concentration of MgO has evident effects on the properties of the MAO coating. When MgO micro-powder increased, the oxide voltage, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] However, hardness is a complex phenomenon, which is related to the structural conguration, chemical bonding, electronic structure, deformation, defects, etc. [10][11][12][13][14] For TMBs superhard materials, previous work has shown that the Vickers hardness is determined by the network and shorter B-B covalent bonds. 15,16 Namely, the boron concentration plays a crucial role in hardness.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] However, hardness is a complex phenomenon, which is related to the structural conguration, chemical bonding, electronic structure, deformation, defects, etc. [10][11][12][13][14] For TMBs superhard materials, previous work has shown that the Vickers hardness is determined by the network and shorter B-B covalent bonds. 15,16 Namely, the boron concentration plays a crucial role in hardness.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the aerospace and automotive industries, the traditional Ni-based superalloys are difficult to meet the requirements of the future hightemperature materials with the high melting point and excellent mechanical properties. [1][2][3][4][5][6][7][8][9] Therefore, it is necessary to explore novel high-temperature structural materials that can be used in higher operating temperatures. [10][11][12][13] Among these high-tempera materials, transition metal silicides have attracted much attention as candidate materials to replace Ni-based superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Therefore, many surface treatments such as microarc oxidation, chemical conversion, and electroless plating are employed to magnesium alloy to improve its corrosion resistance. [7][8][9] It is well-known that electroless Ni-P plating is a preferred way to improve the corrosion resistance and wear property for steel, aluminum, and magnesium alloy of irregular shapes. [10][11][12] While electroless plating directly on magnesium substrate needs to overcome these two difficulties: first, a loose film composed of oxides and hydroxides rapidly formed on the substrate surface weakens the cohesive strength between coating and substrate; second, β phase (Mg 17 Al 12 intermetallic) on the surface is more cathodic than eutectic α and primary α phase, leading to nonuniform coating growth, coating porosity, and failure.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4–6 ] Therefore, many surface treatments such as microarc oxidation, chemical conversion, and electroless plating are employed to magnesium alloy to improve its corrosion resistance. [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%